Corporate governance characteristics and valuation: Inferences from quantile regression - Fekri Ali; Milad Abdelnabi; Hafezali Iqbal; Omar Alaeddin; Omer Bin (Journal of Economics, Finance and Administrative Science, 2016)
Prior literature on corporate governance and performance provides mixed evidence on the impact of various corporate governance measures on performance indicators. However, most of literatures adopt the Ordinary Least Square (OLS). This method is based on the central tendency, which may not appropriately represent the reality in cases where the dependent variable ranges between upper and lower values and hence the relationship may not be homogenous across different percentiles of the dependent variables. A variable having a positive impact based on the central tendency for firms may not be the case for the firms in the upper or lower bounds. Thus, estimating the means using OLS may not reflect and represent the heterogeneity in the estimated relationship. Therefore, quantile regression estimates the relationship at any point conditional on the distribution of dependent variable. This would enable us to generate various estimated coefficient at certain quantile of dependent variable. Therefore, the objective of the study is twofold. First, this study aims to investigate the relationship between corporate governance and performance using OLS. Second, this work further explores the impact of corporate governance mechanisms on performance using quantile regression so as to compare and to shed light on whether there is heterogeneity in the influence of these variables on the performance of listed companies across quantiles. The results of the study provide evidence that quantile approach shows inconsistency in the result with OLS and hence indicating the impact depends on the scale size. This theoretically provides further support that OLS may represent a poor estimation approach for the reality of firms. – – La literatura previa sobre gobierno corporativo y desempe\~no aporta una evidencia mixta del impacto de las diversas mediciones del mismo sobre los indicadores del desempe\~no. Sin embargo, gran parte de la literatura adopta el método de los mínimos cuadrados ordinarios (MCO). Dicho método se basa en la tendencia central, que puede no constituir una representación adecuada de la realidad en aquellos casos en los que la variable dependiente oscila entre los valores superior e inferior y, por tanto, la relación puede no ser homogénea a lo largo de los diferentes percentiles de las variables dependientes. Una variable que tenga un impacto positivo basado en la tendencia central para las empresas puede no ser el caso para aquellas posicionadas en los límites superior o inferior. Entonces, el cálculo de las medias con el uso del método MCO no reflejaría ni representaría la heterogeneidad en la relación estimada. Por ello, la regresión de cuantiles calcula la relación en cualquier punto, supeditado a la distribución de la variable dependiente. Esto nos permitiría generar diversos coeficientes estimados en cualquier cuantil de la variable dependiente. En consecuencia, el objetivo de este estudio es doble: investiga la relación entre el gobierno corporativo y el desempe\~no, utilizando el método MCO y explora el impacto de los mecanismos del gobierno corporativo sobre el desempe\~no, utilizando la regresión de cuantiles, a fin de comparar y arrojar luz sobre la posibilidad de que exista heterogeneidad en la influencia de dichas variables sobre el desempe\~no de las empresas cotizadas, a lo largo de los cuantiles. Los resultados del estudio aportan evidencia acerca de que el enfoque de los cuantiles es inconsistente con el método MCO y, por tanto, indica que el impacto depende del tama\~no de la escala. Esto respalda, además, el hecho de que el método MCO puede representar un enfoque de cálculo más débil para la realidad de las empresas.
Keywords: G30; 330; Performance; Corporate governance; OLS; Quantile regression; Desempe\~no; Gobierno corporativo; OLS; Regresión de cuantiles